P53 protein accumulation in oesophageal squamous cell carcinomas and precancerous lesions. Issue 6 (June 1995) - Volant, A; Nousbaum, J B; Giroux, M A; Roué-Quintin, I; Metges, J P; Férec, C; Gouérou, H; Robaszkiewicz, M
Abstract : AIMS--To investigate the immunohistochemical expression of p53 protein in oesophageal squamous cell carcinomas and in dysplastic areas of the oesophageal mucosa surrounding the tumours. METHODS--Biopsy samples were obtained from 20 patients with an oesophageal squamous cell carcinoma. Blocks of the tumours and of the surrounding mucosa were immunostained with the monoclonal antibody DO-7. RESULTS--Fourteen of the 20 carcinomas were positive for p53 (70%). The frequency of p53 overexpression increased with the differentiation of the tumour. Nine out of 13 dysplastic specimens were positive for p53 (69%): eight cases with severe dysplasia and one case with moderate dysplasia. No p53 immunostaining was detected in normal oesophageal epithelium. All p53 positive dysplastic specimens were taken from the mucosa adjacent to tumours that were also immunostained. In moderate dysplastic mucosa the p53 positive cells were located in the proliferative basal zone, whereas in severe dysplasia the immunostained cells increased in number and spread to upper cell layers of the epithelium. CONCLUSION--This study supports the hypothesis that TP53 gene is frequently involved in the development of oesophageal squamous cell carcinoma and that p53 protein accumulation is an early event in human oesophageal carcinogenesis.